Efficacy of higher‐dose 13.3 mg/24 h (15 cm2) rivastigmine patch on the Alzheimer's Disease Assessment Scale–cognitive subscale: domain and individual item analysis. (18th February 2014) - Alva, Gustavo; Isaacson, Richard; Sadowsky, Carl; Grossberg, George; Meng, Xiangyi; Somogyi, Monique
Abstract Objective Rivastigmine displays dose‐dependent efficacy on cognition in patients with Alzheimer's disease (AD), as measured by the Alzheimer's Disease Assessment Scale–cognitive subscale (ADAS‐cog). Subanalysis of the OPTIMA (OPtimising Transdermal Exelon In Mild‐to‐moderate Alzheimer's disease) study aimed to define ADAS‐cog domains by factor analysis of individual items. Efficacy of 13.3 mg/24 h versus 9.5 mg/24 h rivastigmine patch on individual items and newly derived domains was assessed. Methods OPTIMA was a 48‐week, double‐blind (DB) study in patients with mild‐to‐moderate AD. Patients meeting pre‐defined decline criteria during open‐label treatment with 9.5 mg/24 h patch were randomized in the DB phase to 13.3 mg/24 h (n = 280) or 9.5 mg/24 h (n = 287) patch. ADAS‐cog change from baseline was a co‐primary outcome measure. Factor analysis categorized ADAS‐cog items into newly derived domains. Change from DB‐baseline was calculated for domains and individual items. Results Numerically, less decline was displayed with 13.3 mg/24 h versus 9.5 mg/24 h patch in the total ADAS‐cog score at all time points (significant at Week 24, p = 0.027). Factor analysis identified two domains: memory and language. Significantly, less decline was observed on the memory domain with 13.3 mg/24 h versus 9.5 mg/24 h patch at Weeks 12, 24, and 48 (p < 0.05; observed cases). Three items (following commands, orientation, and word recognition) displayed numerically less decline with 13.3 mg/24 h versus 9.5 mg/24 h patch at all time points. No significant between‐group differences were observed on the language domain. Conclusion Results suggest that the greater cognitive efficacy of 13.3 mg/24 h versus 9.5 mg/24 h rivastigmine patch is driven primarily by effects on memory, particularly in the areas of following commands, orientation, and word recognition. Copyright © 2014 John Wiley & Sons, Ltd.